Löffler's endocarditis. - Scott, M E (1975)
The clinical, laboratory, and necropsy findings in a patient with massive eosinophilia and fatal cardiac failure are reported. Necropsy revealed partial obliteration of the lumen of the left ventricle with dense white thrombus, and fibrous infiltration of the myocardium. An additional finding, not hitherto described in Löffler's endocarditis, was massive enlargement of the mesenteric lymph nodes.